EKSPLORASI PROBLEM BASED LEARNING TERHADAP KREATIVITAS SISWA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI KURIKULUM MERDEKA - Imroatus Sa’idah; Muhammad Odik Afifin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) method in enhancing student creativity and learning independence within the context of the Independent Curriculum at SMP PGRI 01 Gedangan. The method used in this study was qualitative, focusing on the application of PBL in Islamic Religious Education (PAI) learning. The results showed that the implementation of PBL had a significant positive impact on student engagement. This method made the learning process more interesting and relevant to students' daily lives, with an emphasis on social and moral issues, such as interfaith tolerance and ethics in social media. Group discussions allowed students not only to understand religious theory but also to apply it in broader contexts, such as in the theme